2014
DOI: 10.2967/jnumed.113.134981
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-FDG PET in Patients with Infectious Endocarditis

Abstract: It was our purpose to evaluate the clinical impact of systematic PET/CT for the diagnosis of infectious embolisms in patients with infectious endocarditis (IE) in comparison with a historic cohort of IE patients managed without this technique. Detection of extracardiac lesions is an essential component of the management and outcome of IE. Studies using PET/CT for the evaluation of patients with IE are scarce, lack a control group, evaluate a small number of patients, or consist of case reports. Methods: We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 17 publications
3
52
0
Order By: Relevance
“…There is increasing evidence that FDG positron emission tomography (PET)/computed tomography (CT) may be useful in the management of infective endocarditis, both for detection of septic emboli [9][10][11][12][13] and for diagnosis of prosthetic valve infection. [14][15][16] A study showed that the sensitivity of the modified Duke criteria performed at admission was markedly increased when the presence of an abnormal FDG uptake was added as a major criterion.…”
Section: See Editorial By Sambuceti Et Al See Clinical Perspectivementioning
confidence: 99%
“…There is increasing evidence that FDG positron emission tomography (PET)/computed tomography (CT) may be useful in the management of infective endocarditis, both for detection of septic emboli [9][10][11][12][13] and for diagnosis of prosthetic valve infection. [14][15][16] A study showed that the sensitivity of the modified Duke criteria performed at admission was markedly increased when the presence of an abnormal FDG uptake was added as a major criterion.…”
Section: See Editorial By Sambuceti Et Al See Clinical Perspectivementioning
confidence: 99%
“…In a prospective study of patients with a diagnosed native valve infective endocarditis, FDG PET/CT identified additional infection sites in 74.5% of the patients, such as the lungs, skeleton, brain, and other organs. Based on the information of extra-cardiac findings on FDG PET/ CT, the incidence of relapse infective endocarditis was decreased by 2-folds because of appropriate intervention as a result of the extra-cardiac findings on FDG PET/ CT. 18 …”
Section: Prosthetic Vs Native Valve Endocarditismentioning
confidence: 99%
“…If these acral findings exist, the diagnosis may be confused with infective endocarditis especially when valvular involvement is detected on echocardiography. Both FDG and NaF (sodium fluoride) PET/CT imaging can be used to obtain advanced information about the valvular lesions (11,12). In our case, we used NaF PET/CT because of severe calcification on CT.…”
Section: Differential Diagnosis Of Cuamentioning
confidence: 99%
“…In our case, we used NaF PET/CT because of severe calcification on CT. It is a powerful technique to differentiate whether the lesion is due to sole calcification or secondary to other inflammation causes (12). It showed NaF (sodium fluoride) uptakes on the valves with calcified masses.…”
Section: Differential Diagnosis Of Cuamentioning
confidence: 99%